Issues and Challenges of Urban Heritage Trees Conservation in Malaysia Towards a Sustainable Site - Fazamimah Mohd Ariffin, Noor; Azramalina Abdul Aziz, Noor; Ismail, Sumarni (International Journal of Engineering and Technology, 2019)
Now, the rapid development of urban areas has changed the land use of the natural environment to built environment. In Malaysia, this situation causes a lot of urban trees have been felled to make way for urban development. In giving historical identity and cultural symbolic to landscape of the cities, usage of heritage trees are important. Moreover, heritage trees will create emphasize historical environment which give important roles of landscape to the cities. The main objective of this paper is to explore the issues and challenges of urban heritage trees conservation in Malaysia. The goal of this paper is to induce public awareness in conservation of the heritage trees as part of landscape roles to create culture and historical value in cities. This study use case study as a research method to explore the issues and challenges of Malaysia urban heritage trees conservation. Three case studies have been selected which are Taiping Lake Garden, Kuching North City and George Town World Heritage Site based on the existence of heritage trees. An observation and analysis through of past studies have allows the exploration and understanding of the various issue of urban heritage trees conservation in these heritage site towards a sustainable site. The future research to carried out has been founded.Â Â